Design and Synthesis of a Facile Solution‐Processing and Ultrastable Crosslinkable Branched Nitroxide Polymer. Issue 9 (3rd April 2019) - Qin, Herong; Liu, Xiu; Huang, Jianbing; Liang, Hui; Zhang, Zishou; Lu, Jiang
Abstract: A general critical challenge for nitroxide polymers being used as cathode materials is keeping the good solubility during the processing and good solvent resistance during charging and discharging. To address this issue, herein, a new photo‐crosslinkable branched nitroxide polymer is designed and synthesized via reversible addition‐fragmentation chain transfer copolymerization of 2, 2, 6, 6‐tetramethyl‐4‐piperidyl methacrylate, cinnamoyl ethyl methacrylate, and ethylene glycol dimethacrylate, followed by oxidation using 3‐chloroperoxybenzoic acid. The as‐synthesized polymer can dissolve in ethyl alcohol with environmental‐friendly processing, and then can easily change into crosslinked polymer with highly resistance to organic electrolyte after UV irradiation. The crosslinked nitroxide polymer‐based cathode achieves remarkable cycle stability with a capacity retention of 90% over 1000 charge–discharge cycles at 10 C current rate, superior to that of the un‐crosslinked one with capacity retention of 65% over 1000 cycles. Abstract : Photo‐crosslinkable branched organic radical polymers are designed and synthesized for the first time to mix with conductive carbon to obtain a long‐life electrode via the facile solution processing and the following UV‐induced crosslinking. The crosslinked polymer‐based electrode performs quite well with capacity retention of 90% after 1000 cycles.